Effect of Acute and Chronic exposure to Titanium Dioxide Nanoparticles on the weight of body and some organs of Japanese quail - Taha, Ameer M.; Ahmed, Nazhan M. (International Journal of Scientific Research in Biological Sciences, 2023)
The current study was conducted to identify the changes in body weight as well as the weight of the liver and kidneys caused by acute and chronic exposure to Titanium dioxide nanoparticles (TiO2NPs) of Japanese quail Coturnix coturnix japonica. The current study used (75) quail birds, the birds were divided randomly into five groups in each group 15 birds, the first group is the control group that was dosed with 0.5 ml of distilled water for thirty days. The second experimental group was dosed with TiO2NPs at a concentration of 5 mg/kg for thirty days. While the third experimental group was dosed with TiO2NPs at a concentration of 10 mg/kg for thirty days. While the fourth experimental group was dosed with TiO2NPs at a concentration of 20 mg/kg for four days only. The fifth experimental group, which was dosed with TiO2NPs at a concentration of 40 mg/kg for four days only. The birds were weighed before the start of the experiment, then weighing and necropsy were carried out after 4, 14, 30, and 60 days from the start of the experiment. The statistical results showed significant differences in the body weights of quail birds between the control group and the experimental groups, and the second experimental group had a higher weight than the rest of the experimental groups two months after the start of the experiment. Also, significant differences appeared in the weights of the kidneys and liver between the different groups, as all the birds of the experimental groups were less in weight in most periods than the control group. The highest weight of the liver with a significant difference was in the fifth experimental group, two months after the start of the experiment. And the highest weight of the kidney in the same group and for the same period from the start of the experiment.